Lernwelt Hochschule - Stang, Richard; Becker, Alexandra (De Gruyter, 2020)
The college learning environment is in flux. The shift from teaching to learning entails extensive processes of change. A three-year research project conducted by the Learning Research Centers at the Stuttgart Media University studied this topic. This volume provides an exhaustive overview of current developments in the field. The book presents the results of academics research and documents good practice.